If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-24+8a=-3(5a-9)
We move all terms to the left:
-24+8a-(-3(5a-9))=0
We calculate terms in parentheses: -(-3(5a-9)), so:We get rid of parentheses
-3(5a-9)
We multiply parentheses
-15a+27
Back to the equation:
-(-15a+27)
8a+15a-27-24=0
We add all the numbers together, and all the variables
23a-51=0
We move all terms containing a to the left, all other terms to the right
23a=51
a=51/23
a=2+5/23
| 5j+10-3j-8j-50=0 | | -3(7b-9)=-28+6b | | 56p+10=60p-2 | | -27=5(6f+3) | | 0.3d−1/31/3=0.84/7 15 | | 0.3d−1 31 3=0.84/7 15 | | 2x-1+2x-1+2x=20 | | 98-15c=20c-42 | | 2x-1+2x-1+2x=15 | | 8z-4z=15 | | 4-4w+6=74 | | 33=4s+8s | | 27j+12-11j=52 | | 8(1+5h)=-26 | | 21=6+5(n+4) | | 23=4+7(s-5) | | 23=4+7(s-5 | | 3(1-8f)=15 | | 4(5-7c)=19 | | 4(8d+9)=30-6d | | 8(10^3x)=12 | | -3.3n=-1.1 | | -3v-7-8=-20 | | 75x=80(x-1) | | X^2-20x-9750=0 | | 3a-3a=-5 | | 23=9n+3n | | 10/x=3.16227766017 | | 10x=3.16227766017 | | 1+8x+8x=-15 | | 1+2k+4=7 | | -15-6a=3(8a+5) |